ZnO–graphene composites with high photocatalytic activities under visible light. Issue 99 (11th October 2016) - Xu, Junli; Cui, Ya; Han, Yide; Hao, Men; Zhang, Xia
Abstract : Porous ZnO–graphene composites prepared by a chemical corrosion process show good photocatalytic activity under visible light irradiation. Abstract : ZnO–graphene composites were prepared through a simple chemical corrosion process, and their photocatalytic performance on the degradation of methyl orange and water splitting was studied. The results showed that the prepared ZnO–graphene composites have a porous network structure, which is a benefit to the adsorption and mass transfer of dye and oxygen. The best degradation rate was 87% in 180 min under visible light irradiation with 8 mg ZnO–graphene photocatalyst and the rate of water splitting was up to 4.35 mmol g −1 h −1 . The outstanding photocatalytic performance was ascribed to the porous network structure, narrow band energy and electronic properties of the composites. The presence of graphene can promote the separation of photogenerated electrons with holes, and repress charge carrier recombination, which results in an improvement of photocatalytic activity.